2004
DOI: 10.1111/j.1365-2559.2004.01877.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous benign notochordal cell tumours: overlooked precursors of classic chordomas?

Abstract: The study indicated a surprisingly high incidence of intraosseous benign notochordal cell tumours. The anatomical distribution of the tumours was identical to that of classic chordomas. The results support other evidence that classic chordomas develop from intraosseous benign notochordal cell tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
89
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 12 publications
2
89
0
3
Order By: Relevance
“…5,6 They 4 This previous case suggested a small intraosseous benign notochordal cell tumor (described as a benign notochordal lesion in the original paper) located adjacent to the coccygeal chordoma. In addition, two other small benign notochordal cell tumors were evident in the sacrum at a different level.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…5,6 They 4 This previous case suggested a small intraosseous benign notochordal cell tumor (described as a benign notochordal lesion in the original paper) located adjacent to the coccygeal chordoma. In addition, two other small benign notochordal cell tumors were evident in the sacrum at a different level.…”
Section: Discussionmentioning
confidence: 96%
“…However, we documented a histologically confirmed case of classic chordoma arising in a precursor benign notochordal cell tumor and reported the clinicopathological details of intraosseous benign notochordal cell tumors. [4][5][6] Based on the evidence, we concluded that intraosseous benign notochordal cell tumors are benign notochordal cell lesions with potential neoplastic characteristics and possibly serve as the real precursors of classic chordomas. We recently found two interesting cases of microscopic incipient chordomas coexistent with benign notochordal cell tumors in the coccyx, which supports the above hypothesis.…”
mentioning
confidence: 95%
“…These observation were made at autopsy [1]. Since then, a number of such microscopic remnants have been found incidentally at autopsy, generally less than 1 cm [1,8]. More recently, larger intravertebral notochordal lesion seen radiologically have been described.…”
Section: Discussionmentioning
confidence: 99%
“…Benign notochordal cell tumors are intraosseous lesions which can occur along the midline of the craniospinal axis, particularly in the saccrococcygeal or sphenooccipital region [8,10]. A recent autopsy series found BNCTs in 20% of 100 cadavers, with a mean age of 63 years (7 to 82 years), with a distribution of 12% in saccrococcygeal vertebrae, 11.5% in the clival region, 5% in cervical vertebrae, 2% in lumbar vertebrae and none in the thoracic vertebrae [8].…”
Section: Discussionmentioning
confidence: 99%
“…Chordomas have a predilection for the craniospinal axis and are thought to arise from notochordal rests which evolve into nucleus pulposus, explaining the predominant midline and paramedian locations [6]. Newer literature challenges this traditional concept suggesting that chordomas arise from pre-existing benign notochordal cell tumours [7][8][9][10]. Chordomas present between the fourth and seventh decade with a male to female ratio of 2:1 [6,11].…”
Section: Discussionmentioning
confidence: 99%